Enhancing Women Emancipation for Socioeconomic Transformation in and Beyond Nigeria - Salako, Ekima Tina (Advances in Social Sciences Research Journal, 2019)
The persistence of unequal outcomes with the underutilisation of female abilities and restriction of individual opportunities has it concerns partly on socioeconomic transformation and national development. Tradition or culture and religion have dictated men and women relationship for centuries and entrenched male domination into the structure of social organization and institution at all levels of leadership. Even after several decades of massive economic and social change, inequality in socioeconomic outcomes still remains a significant issue. This development has raised several questions which remained largely unanswered and has equally attracted many gender-related studies and intellectual discourse on female liberation. Patriarchy justifies the marginalization of women in education, economy, labour market, politics, business, family, domestic matters and inheritance. This paper examined dimensions of gender inequality and discrimination that excludes women from socioeconomic and political activities. This is detrimental to national cohesion, progress and development of women in any nation. Therefore, efforts must be made to address the very important issue associated with women’s emancipation for socio-economic transformation. The support for women’s emancipation is very germane in the 21st century for national development and transformation. Therefore, it should be vigorously canvassed.